Guidelines for the nomenclature of the human heat shock proteins - Kampinga, Harm H. (Springer Netherlands, 2008)
The expanding number of members in the various human heat shock protein (HSP) families and the inconsistencies in their nomenclature have often led to confusion. Here, we propose new guidelines for the nomenclature of the human HSP families, HSPH (HSP110), HSPC (HSP90), HSPA (HSP70), DNAJ (HSP40), and HSPB (small HSP) as well as for the human chaperonin families HSPD/E (HSP60/HSP10) and CCT (TRiC). The nomenclature is based largely on the more consistent nomenclature assigned by the HUGO Gene Nomenclature Committee and used in the National Center of Biotechnology Information Entrez Gene database for the heat shock genes. In addition to this nomenclature, we provide a list of the human Entrez Gene IDs and the corresponding Entrez Gene IDs for the mouse orthologs.